Історія Гамаліївського Харлампієва монастиря - Чухно, В. (Сiверянський лiтопис, 2011)
Стаття присвячена історії Гамаліївського Харлампієвого монастиря та ансамблю його пам’яток. Статья посвящена истории Гамалеевского Харлампиева монастыря и ансамблю его памятников. I his article deals with a short history of Gamaliivskyi Kharlampievyi monastery and a band of its sights since its foundation up to hour.